RENAL ABNORMALITIES AMONG SICKLE CELL DISEASE PATIENTS IN A POOR MANAGEMENT SETTING: A SURVEY IN THE DEMOCRATIC REPUBLIC OF THE CONGO - Paul Kambale-Kombi; Roland Marini Djang’eing’a; Jean-Pierre Alworong’a Opara; Jean-Paulin Mbo Mukonkole; Vincent Bours; Dieu-Merci Mbumba Lupaka; Serge Tonen-Wolyec; Lucien Bolukaoto Bome; Charles Kayembe Tshilumba; Salomon Batina-Agasa (Mediterranean Journal of Hematology and Infectious Diseases, 2022)
Background & objective: Sickle cell disease (SCD) is now a well-established cause of renal damage. In the northeast of the Democratic Republic of Congo (DRC), SCD is common. However, sickle cell nephropathy remains unstudied in this region. Thus, this study aimed to assess renal abnormalities in SCD patients in Kisangani (northeastern DRC).